(untitled) (Cadernos de Sociomuseologia, 2023)
This article aims to promote discussion around the ethical-aesthetic dimension within science from the perspective of science museums. It is an attempt to bring the scientific field closer to the sphere of the sensitive, noting the importance of the aesthetic experience in science. The aestheticization of science deals with its necessary sensitization considering the discursive prevalence of its modern paradigm; pushing away subjectivity and remaining rooted in the myth of neutrality. In this work we explore the importance of the experience of the outside, the nomadic posture and the refrain in the production of constant movements of (de)territorialization in an attempt to detach from a concept of science that is only normative, for the production of perceptions around the possibility of an ethical science. To this end, science museums as a pedagogical tool serve as a motto in conducting this problematization. Keywords: science museums; ethic; aesthetics; education.